Contribution of multicriteria analysis and GIS in the discrimination of flood risk areas on the Allada plateau in Southern Benin - KPOHA, Josiane Nadège; AKOKPONHOUE, Houngnigbo Bertrand; Orékan, Vincent; Yao Yao, Muller (My University, 2023)
Flood vulnerability mapping and assessment is an important component of flood prevention and mitigation strategies, as it allows the identification of the most vulnerable areas based on the physical characteristics that determine flood propensity. This study aims to identify and map the factors related to flood risk in the Allada Plateau using a multi-criteria approach, in particular the Saaty Hierarchical Analysis Process (HAP) technique and Geographic Information Systems (GIS). The methodology used in this study allowed the identification of six (06) criteria considered relevant and conditioning the floods, namely: drainage density, slopes, rainfall intensity, soil type, land use and population density. All these criteria were defined as raster datasets with a resolution. The AHP technique was used to calculate the weights of the criteria and factors. The relative importance of the selected criteria made rainfall intensity the most important criterion with a weight of 56%, followed by slope with 26%, and finally drainage density with a weight of 12%. The hazard map generated from this combination shows that 25% of the Allada plateau is a high-risk area. As for the vulnerability map, the most important criterion is population density with a weight of 88% followed by land use with 12%. The combination of the two maps in a GIS shows that the areas vulnerable to flooding occupy 35.37% of the study area. The flood risk map obtained from the combination of the hazard and vulnerability map shows that flood risk areas cover 28.68% of the area of the Allada plateau.
Keywords: Hazard; flood; risk; vulnerability; multi-criteria decision analysis.